Ahirani Language Translation with Neural Networks: An English Perspective - Patkar, Uday C.; Bhardwaj, Shikha; Patil, U. S.; Deepak Sinkar, Yogita; Nitin Patil, Ratna; Ganvir, Neha; Bhamare, Om A. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Machine Translation is the process of converting one natural language into another using computer-assisted techniques. The primary objective is to bridge the linguistic divide that exists among individuals, communities, or nations with distinct languages. India, being a multilingual country, features various regional languages spoken across its diverse regions. However, not all Indians are proficient in multiple languages. India recognizes 18 constitutional languages and employs ten widely-used scripts globally. A significant portion of the Indian population, particularly in remote rural areas, lacks proficiency in understanding, reading, or writing English. This underscores the importance of implementing an efficient language translation system. Machine translation systems capable of translating content from one language to another can significantly contribute to the intellectual and cultural enrichment of the Indian population, irrespective of their native languages. Although Marathi is the most prevalent language in the state of Maharashtra, Ahirani is also widely spoken. Given the universality of the English language and the prevalence of Ahirani among Khandeshi people, we propose the development of an English to Ahirani machine translation system using Recurrent Neural Networks (RNNs)..